The impact of water resource constraints on industrial linkages in the Yellow River basin - Lili, Rong; Yanlei, Duan; Shurong, Duan (Frontiers in Environmental Science, 2024)
Purpose Low water resource utilization rate, water environment pollution, and water ecology deterioration are unfavorable factors restricting the high-quality development of the Yellow River basin and the coordinated development of the region, and industrial linkage is an important mechanism to promote the regional “pole-diffusion” effect. Currently, the water resource constraints of the Yellow River basin are close to the upper limit; in this context, how to enhance the industrial linkage between regions, promote the coordinated development of resources and economy in the Yellow River basin, and construct new “growth poles” of high-quality development has become an important proposition. Methods By analyzing the mechanism of water resource constraints affecting industrial linkage and constructing a mediation effect model, we investigate the transmission mechanism of water resource constraints affecting industrial linkage through virtual water trade and optimization of industrial structure. Results The results show that water resource constraints significantly inhibit the development of industrial linkage in the whole basin, but enhance the development of industrial linkage through the promotion of virtual water trade and optimization of industrial structure; in terms of subregions, there are differences in the mediation effect in the Yellow River basin in the regions with advantages in agriculture and animal husbandry, in the regions with advantages in the energy industry, and in the regions with advantages in the emerging industry and advanced manufacturing industry. Inspiration This study has several aims: first, the rational use of the virtual water trade model of the Yellow River basin; second, use of the basin as a whole to promote the upgrading of industrial structure; third, the development of water resource rigid constraints in accordance with local conditions to promote the sustainable development of the economy; and fourth, promotion of the construction of the industrial community of the whole basin to realize the synergistic high-quality development of the Yellow River basin. Marginal contribution In the study of high-quality development in the Yellow River basin, the existing literature focuses on the optimization of the industrial layout and industrial structure based on the theory of resource advantage and industrial division of labor. Based on this, this article analyzes the impact of water resource constraints on the industrial linkage of regions with advantages in agriculture and animal husbandry, energy industry, and emerging industry and advanced manufacturing industry from the perspective of the adaptability of water resources to the layout of productive forces and puts forward the proposal of coordinating the linkage development of industries in the whole river basin, which promotes the research on the relationship between water resources and industries.